Mesenchymal stromal cell isolation from pond slider (Trachemys scripta) adipose tissue obtained during routine neutering: a model for turtle species - Andreoli, Valentina; Vetere, Alessandro; Conti, Virna; Gavezzoli, Martina; Berni, Priscilla; Ramoni, Roberto; Basini, Giuseppina; Nardini, Giordano; Pelizzone, Igor; Grolli, Stefano; Di Ianni, Francesco (Frontiers in Veterinary Science, 2025)
IntroductionMesenchymal stromal cells (MSCs) hold great clinical potential in veterinary regenerative medicine. However, a notable gap exists in the literature regarding the isolation and characterization of these cells in reptiles. The objective of this study was to evaluate the feasibility of isolating adipose tissue-derived mesenchymal stem cells (MSCs) from pond slider (Trachemys scripta) tissue samples collected during routine neutering procedures.MethodsAdipose tissue samples were obtained from five animals and processed using an enzymatic procedure. The resulting cell suspension was subsequently cultured at 28°C in a controlled atmosphere with 5% CO2. The cell growth rates were evaluated through direct counting of cells up to passage 7. The colony-forming unit (CFU) capacity of MSCs was evaluated in low-density cell cultures, and the ability of the cells to differentiate into adipogenic, chondrogenic and osteogenic lineages was assessed. The cell phenotype was characterized at the molecular level using reverse transcription-polymerase chain reaction (RT–PCR) and amplicon sequencing, with a focus on markers commonly used for gene expression profiling of mammalian MSCs.ResultsThe cells demonstrated the capacity to differentiate into adipogenic, chondrogenic, and osteogenic lineages. RT–PCR revealed the expression of CD105, CD73, CD44, and CD90, whereas CD34 and HLA-DRA were not expressed. Sequence homology analysis demonstrated that the amplicons matched the sequences reported in the Trachemys scripta whole-genome shotgun sequence. This study represents the first investigation aimed at the isolation, in vitro expansion, and characterization of reptile adipose tissue-derived MSCs.DiscussionThe results demonstrate the feasibility of isolating MSC-like cells from chelonian adipose tissue and underscore their potential for application in regenerative medicine for both companion reptiles and endangered wild species.